THE FORMATION, SETTLEMENT LAWS AND MATERIAL COMPOSITION OF GOLD MINING IN THE CENTRAL KYZYLKUM AUMINZA MOUNTAINS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
As a result of the geological-research works and scientific-research works carried out in our republic in recent years, certain progress is being made in expanding the base of mineral raw materials. In particular, as a result of the work carried out, new gold mines and representatives were identified in the Central Kyzylkum region. Through these researches, gold deposits and representatives were found in the center of the Auminza mountains, and based on the study of the geological structure of this new area, determining the characteristics of the location of the ore in the fields is of great scientific importance and remains one of the main directions of exploration. The search, evaluation and search conducted in the research area is an urgent issue, as it has the attention of many researchers. It reflects the results of the study of the formation of the gold mineralization of the Auminza mountains in Central Kyzylkum, the location of their mines, and their material composition. In the research area, the ore-covering rocks consist of volcanic-sedimentary structures of the auminza, tasqazgan and besapan suites, which are mainly composed of mica, carbon-mica, feldspar-chlorite-mica shales, metaaleurolites and sandstones.